THE IMPLEMENTATION OF PQ4R STRATEGY IN TEACHING NARRATIVE READING TEXT (RETAIN, 2020)
PQ4R strategy is a learning strategy which has a good concept to teach the students in comprehending a reading text. Moreover, this study is aimed to find out the implementation of PQ4R strategy in teaching narrative reading text done by the teacher in the classroom. This study is also trying to find out the students’ reading comprehension after practicing the PQ4R strategy in teaching and learning activities. The base of this study is using descriptive qualitative as the research design through an observation. Furthermore, the field notes were used to collect the information regarding teaching and learning process by using the implementation of PQ4R strategy. In one meeting, the teacher implements the stages of PQ4R strategy starting from preview, question, read, reflect, recite, and review sequentially. The implementation of those stages was divided into three reading activities; pre reading, while reading, and post reading. The data from the field notes showed that in pre reading activity, the teacher mostly implemented preview and question stage. In post reading activity, the teacher applied review stage to ensure the students’ understanding about the text by delivering ideas and providing suggestions. The rest of the selected stages read, reflect, and recite applied during while reading activities. Moreover, the students’ reading task was used in order to know the students’ reading comprehension after the implementation and it was analyzed by using ESL Composition Profile considering that the task was in the form of writing a summary towards the reading text. Furthermore, all of those stages of PQ4R strategy and their implementation are useful for the teachers or other educational practitioners when they engaging the students’ reading comprehension in narrative reading text. Keywords: PQ4R strategy, reading comprehension, narrative text.